The Design of a Public Relations Services Information System for Creative Media State Polytechnic Using the Agile Development Method - Yuliana, Citra Ayu; Kartika, Tipri Rose; Mawardi, Cholid (Institut Teknologi Bisnis AAS Indonesia, 2025)
Vocational colleges play a crucial role in producing a work-ready human resource with skills that align with industry demands through practice-based learning and direct application. In this context, effective communication between vocational colleges and prospective students becomes a critical aspect. One form of this communication is introducing vocational education through promotional and outreach activities conducted by the Polimedia Public Relations (Humas) department. The